The Challenges of Changing Active to Passive Voice Towards the Third Grade Students of Muhammadiyah Tangerang University - Imtihan Hanim; Bella Putri Lesmana; Fatimah Fatimah; Tasya Anjili Sabian; Putri Amelia Nur Jam Jami (Journal on Education, 2024)
Grammar seems to be an unavoidable challenge for most learners, especially when it comes to acquiring Active to Passive Voice. Active sentences are sentence patterns where the subject does work, and passive sentences are sentence patterns where the subject accepts work. This is a difficult time for English Education students at Muhammadiyah University, Tangerang. The purpose of this research is to find out students' challenges in learning Active to Passive Voice and how they deal with these problems. The selected participants were 12 students from the Intermediate English Grammar Class of 2022. The research method used was qualitative. Data collection was carried out through tests and interviews. The data shows that students have three major difficulties in changing Active to Passive Voice such as placing subjects and objects, using auxiliary verbs, and determining past participles. In addition, two strategies are used by students to overcome learning obstacles. Through understanding formulas to help them master active and passive learning and doing a lot of active and passive exercises to help them better understand the active and passive material.